Two new African and Madagascan species of the genus Holochlora (Orthoptera: Tettigoniidae, Phaneropterinae) - Bruno Massa (Fragmenta entomologica, 2017)
Two new species, Holochlora mauritiana and H. ingrischi from the island of Mauritius and Zimbabwe, respectively, are described. Along with a third species, H. biloba Stål, 1874 from Madagascar, they are the sole African representatives of the mostly Oriental genus Holochlora Stål, 1873, including ca. 60 taxa distributed from India to China. Preliminary hypotheses on biogeographical and evolutionary origin of Afro-Madagascan Holochlora species are shortly discussed.